An introduction to political communication - McNair, Brian (Communication and society, 2011)
In this new edition, the author offers a broad critical preface to the relationship between politics, the media and democracy in the UK and other contemporary societies. Clearly written, the book helps students cover key concepts and debates in political and media studies.